Interface Mechanics and its Correlation with Plasticity in Polycrystalline Metals, Polymer Composites, and Natural Materials. (2017) - Verma, Devendra; Prakash, Chandra; Tomar, Vikas
Abstract: The interfaces in a composite material have finite thickness up to few micrometers, and have a significant effect on its mechanical strength. In this work, interfaces in polymer composites, and natural materials are analyzed under quasistatic and dynamic loading conditions to obtain interfacial constitutive response at strain rates from 10 -2 to 10 3 s -1 using a new technology called nanomechanical Raman spectroscopy. The interface stresses, interface elastic constants, and interface stress-strain is obtained for the glass/epoxy interfaces along with a power law constitutive model to predict the interface deformation behavior with a dependence on both strain rate and interface thickness.